Proposal for a compact neutron generator based on a negative deuterium ion beam. Issue 1 (1st January 2023) - Jimbo, Kouichi; Shirai, Toshiyuki; Leung, Ka-Ngo; Bibber, Karl van
Abstract: Interest in high intensity generators of neutrons for basic and applied science has been growing, and thus the demand for an economical neutron generator has been growing. A major driver for the development of high intensity neutron generators are studies of neutron disturbance in integrated circuits, for which a compact generator that can be easily accommodated in an ordinary size lab would be highly desirable. We have investigated possible designs for neutron generators based on the D-D fusion reaction, which produce direction dependent mono-energetic neutrons with carry-off energy larger than 2.45 MeV. Specifically, we find a negative deuterium ion beam most attractive for this application, and plan to construct such a system with a negative deuterium ion beam of 200 keV energy and 100 mA current as a prototype of this concept.